HARGA OPTIMALTIKET MASUK WISATA ALAM BANTIMURUNG, SULAWESI SELATAN - wahyudi isnan (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
The number of visitors to the Bantimurung natural park fluctuated allegedly due to the increase of the price of admission ticket. The aim of the study is to analyze optimal price of admission ticket and willingness of visitors to pay admission ticket to the Park. The study was conducted in Bantimurung natural park, South Sulawsi, from January to April 2013.117 number of samples was taken by using convenience sampling method. Analysis of optimal prices and the willingness of visitors to pay for ecotourism to the Park were conducted by creating tourism demand function, which then simulated the price of admission, into the equation function of tourist demand. The results showed that the optimal price of the admission ticket was at the price of Rp75,000. At the optimal price of admission ticket of Rp75,000 the Park would earn revenues of Rp18,230,700,000. An average value of the visitor willingness to pay was Rp118,032, with price of admission ticket was Rp75,000, then, the average visitor will get consumer surplus of Rp43,032. If the management of Bantimurung natural park desiring to increase the total revenue, then the price of admission ticket can be increased to be Rp75,000.